SAT0151 Safety Profile of BOW015, A Biosimilar Infliximab, In Healthy Subjects and Patients with Active Rheumatoid Arthritis. (9th June 2015) - Kay, J.; Lassen, C.; Trokan, L.; Wyand, M.
Abstract : Background: BOW015 is being developed as a biosimilar of reference infliximab (rIFX, Remicade®). Bioequivalence of BOW015 and rlFX was assessed in healthy subjects and their therapeutic equivalence was assessed in patients with active rheumatoid arthritis (RA). 1, 2 Here, we summarize safety data from these two studies. Objectives: To determine safety, tolerability and immunogenicity of BOW015 to rIFX. Methods: Safety of BOW015 was assessed in a Phase 1, randomized, double-blind (DB), parallel-group, single-dose, single-center study in 84 healthy Caucasian male volunteers, and in a Phase 3, randomized, DB, active comparator study in 189 patients with active RA. In the Phase 1 study, subjects were administered a single 5 mg/kg IV infusion of BOW015 or rlFX, and then were followed for up to 12 weeks (wks). In the Phase 3 study, patients with active RA (87.8% female; mean age, 44.8 years) receiving stable methotrexate doses (10-20 mg/wk) and were randomized 2:1 to receive either BOW015 or rlFX 3 mg/kg IV at wks 2, 6 and 14, with follow-up at wk 16. In the open-label (OL) phase, responders to BOW015 or rIFX (n=157) received BOW015 3 mg/kg IV every 8 wks at wks 22, 30, 38 and 46, with follow-up at wk 54. Safety assessment included monitoring of adverse events (AEs), vital signs, clinical laboratory parameters, anti-drug antibodies, and 12-lead electrocardiography. Results: Overall frequency of AEs in both studies is summarized in the Table . In the Phase 1 study, 88% of treatment emergent AEs (TEAEs) were of mild intensity and none caused study withdrawal. Nasopharyngitis was the most common TEAE in both groups. In the Phase 3 study, pyrexia and infections occurred more frequently among subjects treated with BOW015 than with rlFX during the DB phase: 8 (6.3%) vs 0% and 21 (16.5%) vs 6 (9.7%), respectively. The reported infections did not cluster by symptom or type. Safety and tolerability of BOW015 continued to be similar to that of rIFX in the OL phase, during which 78 (49.7%) subjects reported TEAEs, 44 (28.0%) reported TEAEs related to study drug, and 10 (6.4%) reported serious TEAEs. Immunogenicity of BOW015 was similar to that of rIFX in both studies and is summarized in the Table . In the Phase 1 study, 2 subjects receiving rlFX developed a positive QuantiFERON®-TB Gold test result at wk 12. During the DB phase of the Phase 3 study, 3 cases of TB were reported among subjects receiving BOW015 and none were reported among subjects receiving rlFX. Two additional cases of TB were reported during the OL phase. Conclusions: In both the Phase 1 and Phase 3 studies, safety, tolerability and immunogenicity of BOW015 and rlFX were similar. Taken in combination with analytical, pharmacokinetic, and efficacy data, these results establish biosimilarity between BOW015 and rIFX. References: Kay J et al. Ann Rheum Dis 2014; 73(Suppl2):64. Kay J et al. Arthritis Rheumatol. 2014; 66(12):3538. Acknowledgements: This research was sponsored by EPIRUS Biopharmaceuticals Inc. Disclosure of Interest: J. Kay Grant/research support from: AbbVie Inc.; Eli Lilly and Company; Pfizer Inc.; Roche Laboratories, Inc. (paid to the University of Massachusetts Medical School), Consultant for: Amgen, Inc.; AbbVie Inc.; AstraZeneca; Boehringer Ingelheim GmbH; Bristol-Myers Squibb Company; Eli Lilly and Company; Epirus Biopharmaceuticals Inc.; Genentech Inc.; Hospira, Inc.; Janssen Biotech, Inc.; Merck Sharp & Dohme Corp.; Nippon Kayaku Co., Ltd.; Novartis Pharmaceuticals Corporation; Pfizer Inc.; Samsung Bioepis; Roche Laboratories, Inc.; UCB, Inc., C. Lassen Employee of: Epirus Biopharmaceuticals Inc., L. Trokan Employee of: Epirus Biopharmaceuticals Inc., M. Wyand Employee of: Epirus Biopharmaceuticals Inc.